Extensive Reading in Action: Voices from the Grounds - Dzulfikri Dzulfikri; Ali Saukah (Intelektual Pustaka Media Utama, 2017)
This study is aimed at investigating how extensive reading affects students’ reading attitude and comprehension. Based on two participants’ pretest and posttest results and analyzing the results of interviews, the study reveals that extensive reading tends to promote participants’ reading comprehension as indicated by the improvement of their scores in posttest and participants’ reading attitude as indicated by their responses to interviews. Their positive attitude develops particularly because of the autonomy given to them to select any materials in their interest as when finding interesting reading texts beyond their current linguistic competence, which is not recommended to read in extensive reading, they struggle to understand them regardless of their reading proficiency. Their positive attitude is also shown by their increasing reading amount week after week and their dreams to have a private library and be lifelong readers. Moreover, exposure to a large number of different texts, a large array of words, and different topics enables them to build background knowledge which helps them understand texts better which subsequently affects their reading ability positively.